Lymphocyte-to-Monocyte Ratio is a Good Marker of Adhesive Capsulitis in Rotator Cuff Tears - Seyit Ali Kayış; Emre Arıkan; Tacettin Ayanoğlu; İlhan Çelik; Hümeyra Çelik (Acta Medica Alanya)
Aim: The aim of the study is to evaluate the prediction of adhesive capsulitis in the preoperative period of rotator cuff tear (RCT) by neutrophil-lymphocyte (NLR), platelet-lymphocyte (PLR), neutrophil-monocyte (NMR), lymphocyte-monocyte (LMR) ratios.Methods: This study was designed as a retrospective case-control study. After ethical approval, preoperative hemogram and biochemistry data of 128 patients who were operated on for RCT were collected from the archive of hospitale. Among the patients who underwent arthroscopy due to RCT, those with signs of adhesive capsulitis in the intraoperative period were included in the RCT+Adhesive capsulitis group. Age, blood glucose, CRP, sedimentation, white blood cell, neutrophil, monocytes, lymphocytes, platelets, fasting blood glucose, hemoglobin and hematocrit values, and NLR, PLR, NMR, and LMR ratios were compared between healthy control and RCT+Adhesive capsulitis. Logistic regression analysis of the ratios was also performed.Results: A total of 64 healthy RCT (group 1) and 64 patients with RCT+Adhesive capsulitis (group 2) were included in the study. Fasting blood glucose, lymphocyte, CRP values, and NMR and LMR were found to be higher in patients with adhesive capsulitis (p<0.05); and monocyte, NLR and PLR were found to be lower in group 2 compared to group 1 (p<0.05). According to ROC analysis, it was revealed that LMR was the best predictor of adhesive capsulitis in RCT.Conclusion: It has been demonstrated that the inflammation rate LMR obtained from the hemogram, which is an easy, low-cost, and reproducible method, is a variable that predicts adhesive capsulitis in RCT.